Is There a Relationship Between Acute Coronary Syndrome and Prostate Specific Antigen Level? - Durmaz, Tahir; Ayhan, Huseyin; Keles, Telat; Bilen, Emine; Akcay, Murat; Akar Bayram, Nihal; Bozkurt, Engin (Urology Journal, 2014)
Purpose: Interestingly, prostate-specific antigen (PSA), which is used to monitor prostate disorders, has been suggested to be beneficial in estimating prognosis associated with coronary artery disease (CAD). The aim of the present study was to investigate the relationship of serum levels of PSA and free PSA (fPSA) with prognosis of acute coronary syndromes (ACS), extent of CAD and major adverse cardiac events in patients with acute coronary syndromes. Materials and Methods: Sixty-seven male patients who were diagnosed with acute coronary syndromes were included. All patients were assessed according to the Thrombolysis in Myocardial Infarction (TIMI) classification [ST elevation myocardial infarction (STEMI) and non-ST elevation (NSTE)-ACS groups, separately], the Global Registry of Acute Cardiac Events (GRACE) (difference between PSA and fPSA) risk score and the Killip classification. All patients underwent angiography. The degree of stenosis was scored using the Gensini score to assess the extent of CAD. Results: Serum PSA, fPSA, fPSA/PSA levels, and alpha 1-antichymotrypsin-PSA (ACT-PSA) (difference between PSA and fPSA) results were found to be moderately correlated with the TIMI and GRACE risk scores, which are predictors of short- and mid-term prognosis. While there was no correlation between the Gensini score and PSA and ACT-PSA, the Gensini score was moderately correlated with fPSA and fPSA/PSA. There were no significant differences between patients with major adverse cardiovascular events (MACEs) and those without MACEs at the 6-month follow-up in terms of PSA, fPSA, fPSA/PSA, and ACT-PSA results. Conclusion: There may be a relationship between serum PSA and fPSA levels and prognosis of ACS and extent of CAD. It should be kept in mind that additional biomarkers could be used together with current scoring systems in risk classification in cases for which clinical decisionmaking is challenging. Moreover, PSA and fPSA results should be approached with caution in patients to be screened for prostate cancer as their serum levels may be influenced from several factors (ACS, infection, etc.).